DEVELOPMENT OF PROPERTY AND REAL ESTATE COMPANIES: Z-SCORE METHOD APPROACH - Yuniarwati , Yuniarwati; Yusianto, Yusi (Graduate Program of Universitas Tarumanagara, 2023)
This research aims to evaluate the development of public companies in the property and real estate sector from 2017 to 2020. The method used to assess such development is the Z-score model. The Z-score model classifies the company into three conditions: safe, gray, and distress. The study showed that of the 40 companies studied, most companies, above 72.5%, fall into the safe category. Companies that fall into the gray area category are second, and companies in the distress category are third. From 2017 to 2020, companies that fall into the safe category tend to decline. On the other hand, companies that fall into distress tend to increase.